A submarine depth control system design - LICEAGA-CASTRO, E.; VAN DER MOLEN, G. (International journal of control, 1995)
Submarines operating at deep submergence can be considered to be in a disturbance-free environment. Under these conditions the design of depth-keeping controllers is a straightforward task. At shallow submergence under rough sea conditions and at low speed, accurate depth-keeping controller designs require particular attention. In these circumstances, the submarine is subject to severe disturbances, imposing additional restrictions on the designer. A submarine low-depth multivariable autopilot has been developed by applying classical Bode and Nyquist techniques. It is shown that a successful multivariable depth-keeping autopilot design can be produced using the framework of individual channel design. It is also shown that, the performance of the resulting linear fixed controller obtained, can be extended to a wide range of the submarine's operational envelope. This is achieved by considering the nonlinear effect of the speed on the nominal design. With such a modification, there is no need to implement a complex controller scheduling process. One advantage of the approach proposed here, is that the robustness of the multivariable control system can be stated in terms of actual gain and phase margins. The autopilot performance and robustness have also been assessed through a series of nonlinear simulations.